Integration of Artificial Intelligence (AI) in the Transformation of Islamic Education Learning Strategies in Higher Education - Khotimah, Husnul; Janah, Miftahul (Proceeding International Conference on Education, 2025)
The advancement of artificial intelligence (AI) has had a significant impact on learning strategies in higher education, including in Islamic studies courses. This study aims to examine the form of AI integration in Islamic Education learning and its impact on the effectiveness and internalization of Islamic values of students. The research method used a descriptive qualitative approach with a case study strategy, implemented in the Islamic Education Study Program, Faculty of Tarbiyah, UIN Syekh Wasil Kediri. Data were obtained through in-depth interviews, observation, and documentation, then analyzed using the Miles Huberman interactive analysis model. Data validity was carried out through triangulation techniques of sources, techniques, and time. The results of the study indicate that there are seven forms of AI integration in the transformation of Islamic Education (PAI) Learning Strategies in higher education, namely AI integration in pedagogical aspects, the role of lecturers, interaction, access to materials, assessment, values and spirituality, and personalization. This form of AI integration has been proven to increase learning independence, flexibility of access, and student engagement. However, challenges arise related to ethics, reduction of spiritual values, and potential content bias, which require the role of lecturers as companions and interpreters of values. Therefore, the transformation of AI-based learning in Islamic Education learning must be carried out in an integrative manner while maintaining Islamic pedagogical principles and digital civilization values